Aktivitas Penyembuhan Luka Sediaan Topikal Ekstrak Bawang Merah (Allium cepa) terhadap Luka Sayat Kulit Mencit (Mus Musculus) (THE ACTIVITY OF TOPICAL EXTRACT OF ONIONS (ALLIUM CEPA) ON WOUND HEALING PROCESS IN MICE (MUS MUSCULUS)) - Yunanda, Visa; Rinanda, Tristia (Jurnal Veteriner, 2017)
Wound healing is a physiological response of the body to restore continuity, structure and function ofthe injured tissue. Onion is one of the plants that are empirically used by the community to heal wounds.The purpose of this study was to observe the effect of topical extract of onions (Allium cepa) on woundhealing process in mice (Mus musculus) strain BalbC. This study used the posttest-only control groupdesign with completely randomized design (CRD). The samples were 12 male mice with weight ranged of22-32 g divided into four treatments; i.e.: Vaseline, topical extract of onion 5%, topical extract of onion30% and topical extract of onion 55% with 3 replications. Wound healing evaluated macroscopically toobserve hyperemia, wound contraction, granulation, crusting and pus production; and microscopically bycounting the number of fibroblasts on day 10. Hyperemia, granulation, crusting and pus production wereanalyzed descriptively. Wound contraction and the number of fibroblasts were analyzed using ANOVA(p<0.05) and followed with Duncan’s test (p<0,05). Descriptive observations obtained hyperemia lasteduntil day 3, granulation in wounds used topical extract of onion 30% and 55% were faster than the other,crusting lasted until day 6 and the production of pus was not found in any treatment. Statistical testresults showed that topical extract of onion 55% significantly affected wound contraction and topicalextract of onion 30% and 55% significantly affected maturation, which characterized by the decreasednumber of fibroblasts. The results of this study showed that topical extract of onion had significant effect(p<0.05) on wound healing and the effect was in line with the increased concentration of the onion extract.
Keywords: topical extract of onion: Allium cepa; wound healing